Efficacy of pegylated interferon alfa-2b «Algeron» in the treatment of chronic hepatitis C - M. V. Mayevskaya; O. O. Znoyko; E. A. Klimova; S. L. Maximov; S. N. Kizhlo; N. A. Petrochenkova; F. I. Nagimova; R. A. Ivanov; Yu. N. Linkova; T. V. Chernovskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the study. To compare efficacy and safety of Algeron 1.5 and 2.0 μg/kg with PegIntron in combination with ribavirin in the treatment of chronic hepatitis C and to determine therapeutic dose of Algeron.Materials and Methods. 150 adult treatment-naive patients with HCV (all genotypes)were randomized into 3 groups. In the two main groups the patients received Algeron in the dosage of 1.5 or 2.0 μg/kg/week, in the active control group – PegIntron 1.5 μg/kg/week in combination with ribavirin. Primary efficacy endpoints were rapid and early virologic response (RVR and EVR).Results. Comparative analysis of virologic response rate after 4th and 12th weeks of the therapy and biochemical response did not show any statistically significant differences between the groups. RVR was observed in 64% and 56% of patients receiving Algeron 1.5 and 2.0 μg/kg, respectively, in the PegIntron group – in 66% (mITTanalysis, p>0,05).The frequency of EVR in Algeron groups after 12 weeks of treatment (regardless of a dose – 1.5 or 2.0 μg/kg) was 94%, in the reference group (PegIntron) – 88% (p>0,05). RVR and EVR rate analysis according to HCV genotype also did not showed statistically significant differences between the groups. Safety profiles of Algeron and PegIntron were similar. The complex assessment of the efficacy and safety allowed to make the conclusion about the optimal therapeutic dose of Algeron, equal to 1.5 μg/kg/week.Conclusions. Results of the study provide evidence of the high efficacy and safety of Algeron for suppression of HCV replication and make it possible to recommend Algeron 1.5 μg/kg weekly in combination with ribavirin for the treatment of chronic hepatitis C in treatment-naÏve patients for 24–48 weeks depending on the HCV genotype.